Pengaruh Ekonomi Durasi Proyek Produksi Karpet Dengan Metode CPM di CV Natural Palembang - Juliska, Brigita Maria; Alfian, Achmad (Universitas Multi Data Palembang, 2025)
CV Natural Palembang is one of the local trading companies and exports of carpets and other furniture. The Production Department has a sub-division, namely the manufacture of carpets made from abaca tree fiber which is currently a mainstay product. For sales, especially exports that have a delivery deadline agreement so that delays must be avoided. Currently, production is experiencing some delays because production scheduling is still done manually with estimated time. These delays impact financial performance— the more delays occur, the higher the penalties, resulting in economic losses. The study was conducted by collecting data on the duration of each production process activity and calculating using the CPM (Critical Path Method) method and then analyzing the critical path and activities and optimum time. Based on the CPM calculation, the critical path is obtained, namely the 2nd activity path with the series AàCàDàEàGàHàIàJàK. The calculation results show that the total optimal time obtained is 19.5 hours, in other words 4.5 hours faster than the company's actual production time, which is 24 hours for 1 carpet. This time optimization leads to cost savings of IDR 3,920,000.